Lack of Conventional Acinar Cells in Parotid Salivary Gland of Patient Taking an Anti-PD-L1 Immune Checkpoint Inhibitor - Pringle, Sarah; van der Vegt, Bert; Wang, Xiaoyan; van Bakelen, Nico; Hiltermann, T. Jeroen N.; Spijkervet, Fred K. L.; Vissink, Arjan; Kroese, Frans G. M.; Bootsma, Hendrika (Frontiers in Oncology, 2020)
Background Salivary glands (SGs) can be damaged by immune checkpoint inhibitor (ICI) therapy. In patients with ICI-induced SG dysfunction, 60% progress to fulfill classification criteria for primary Sjögren’s syndrome (pSS), owing to immune foci in SGs and/or anti-SSA autoantibody positivity. We report the SG tissue analysis of a patient with SG dysfunction after treatment with a programmed death ligand-1 (PD-L1) inhibitor, compared to that of a dry mouth (‘sicca’) control and pSS patient. Case report The patient received the PD-L1 inhibitor durvalumab (10mg/kg, every 2 weeks by intravenous infusion) as adjuvant treatment for stage 3 non-small cell lung carcinoma, following concurrent chemo radiotherapy. At 43 weeks after 21 cycles of Durvalumab, the patient was not capable of producing unstimulated or stimulated parotid gland saliva, and a biopsy was taken. Immunohistochemical analysis showed no classical AQP5+ CK7- acinar cell clusters (CK7 marks intercalated ducts, IDs). In contrast, the parenchyma was dominated by hybrid epithelial ‘structures’ with ID-like morphology, containing a mixture of AQP5+CK7-, AQP5-CK7+ and AQP5+CK7+ cells (30 structures/mm2). These structures were present at lower frequencies in sicca control (2/mm2) and pSS (10/mm2) tissue. Hybrid structures contained proliferating (Ki67+) cells and senescent (p16+) cells. Striated ducts showed no abnormal morphology post PD-L1 treatment, in contrast to pSS tissue. PD-L1 expression was detected in the SG parenchyma following anti-PD-L1 therapy. The SG post-PD-L1 therapy further demonstrated focal lymphocytic sialadentitis, harboring disperse and focal CD4+ T cell-rich infiltrates. CD8+ T cells were also present. In this patient, these CD4+ and CD8+ T cells were observed in-between and inside hybrid structures. CD20+ B-cells were infrequently detected following PD-L1 blockade, in contrast to their preponderance in pSS SG tissue. Conclusion This patient lacked conventional SG acinar cells following anti-PD-L1 therapy and demonstrated presence of hybrid intercalated duct-like structures. Understanding which mechanisms and dynamics underpinning this aberrant parenchyma may be crucial to understand how SG dysfunction post ICI therapy, and potentially other affected organs. Furthermore, although the patient treated with anti-PD-L1 antibody examined here fulfills the criteria for pSS and demonstrated focal lymphocytic sialadentitis, the further histopathological characteristics do not resemble pSS.